An Analysis of Blockchain Adoption in Supply Chains Between 2010 and 2020 - Vadgama, Nikhil; Tasca, Paolo (Frontiers in Blockchain, 2021)
In this research, the evolution of blockchain applied to supply chains has been mapped from the inception of the technology until June 2020, utilising primarily public data sources. We have analysed 271 blockchain projects on parameters such as their inception dates, types of blockchain, status, sectors applied to and type of organisation that founded the project. We confirm generally understood trends in the blockchain market with new projects following the industry's general hype and funding levels. We observe most activity in the Agriculture/Grocery sector and the Freight/Logistics sector. We see the shift of market interest from private companies (startups) to public companies and consortia and the change in blockchain adoption from Ethereum to Hyperledger. Finally, we observe more market-ready solutions and fewer inactive projects for Hyperledger-based projects than Ethereum-based projects.